Macroporous diamond foam: A novel design of 3D interconnected heat conduction network for thermal management. (15th October 2018) - Ye, Wentao; Wei, Qiuping; Zhang, Long; Li, Haichao; Luo, Jingting; Ma, Li; Deng, Zejun; Lin, Cheng-Te; Zhou, Kechao
Abstract: Diamond with a 3D porous macrostructure has a combination of outstanding intrinsic physicochemical properties and unique structural advantages, which is highly promising for wide-scale practical applications. In this paper, a novel macroscopic porous structure of diamond foam (DF) prepared by hot filament chemical vapor deposition (HFCVD) is proposed for thermal management. The continuous diamond film coated on macroporous Cu foam (CF) substrate forms a monolith of 3D interconnected diamond network, which can act as an effective conductive highway for heat transfer, leading to an exceptional thermal transport property significantly superior to that of CF. Then, DF was further infiltrated with epoxy resin as a thermal conducting filler through the vacuum impregnation process. The thermal conductivity of DF/epoxy composite significantly increased up to 10-fold from 0.23 (neat epoxy) to 2.28 W/m K even with a fairly low diamond loading of 1.2 wt%. The further finite element analysis indicates that the formation of 3D interconnected heat conduction network is advantageous to dissipate heat efficiently in practical application. This work opens up new opportunities toward realizing the application of macroporous DFs and their composites for the use in heat dissipation and the future development of high-performance thermal management systems. Graphical abstract: Highlights: Macroporous diamond foam is fabricated by chemical vapor depositing continuous diamond films on Cu foam. The well-bridged CVD diamond grains are favorable to form the fast conductive channels for heat transfer. A novel 3D diamond foam reinforced epoxy composite is designed and fabricated. The thermal conductivity of diamond foam/epoxy composite increases by 891% at low diamond loading of 1.2 wt%. The formation of 3D interconnected heat conduction network is beneficial for heat dissipating efficiently.